Education on making natural herbal soap made from waste cooking oil - Rahma Diyan Martha; Ika Rachutami; Danar Danar (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Waste cooking oil (WCO) resulted from the frying process with the same cooking oil repeatedly. The use of used cooking oil can pose a danger to the human body, and the continuous disposal of used cooking oil harms the environment and the sustainability of human life. This problem was found in Wates Village, Sumbergempol District, especially housewives who are also members of the Rukun Makmur KRPL in the village. This community service aims to provide socialization and training (education) in making soap made from used cooking oil. The method used in this activity is lecture and discussion. COVID and posttest are carried out before and after the activity, which is one form of evaluation. The activity results showed that counseling and training on soap making had provided new information and knowledge to KRPL mothers in Rukun Makmur, Wates Sumbergempol Village, Tulungagung Regency, and provided skills to make soap from used cooking oil. This activity has been able to be followed and carried out well by the participants.